PENCIPTAAN LUKISAN BERBASIS BENTUK SENI RUPA ETNIK KARO PADA MATRA KERET YANG DIBENTUK DENGAN ALAT PENGANTAR PANAS - Zulkifli Zulkifli; Dermawan Sembiring; Wahyu Tri Atmojo; Mangatas Pasaribu (BAHAS, 2018)
The article, a result of this research, discusses the creation of art painting based on ethnic visual art of Karo, which is expressed on rubber material dimension formed with heat conductor device. The purpose is to find the form of North Sumatera’s visual art which is particular and unique. Therefore, it can contribute to the enrichment of the local and national cultural value. The method used is survey method and creative creation method. The testing of the result of the creation was done through the assessment of competent critics and appreciative response of the observers and the community. The data analysis was conducted with the quantitative and qualitative descriptive method. The result of this research shows that the character of Karo ethnic’s visual art as the basis of the art paintings’ development is commonly decorative and mythical. Rubber material as screen area with heat conductor is quite effective to explore the real texture and relief image, as well as producing artistic effect when exposed with light. Based on the critics’ and the observers’ appreciative response, the created works have had the quality of intra-aesthetic and extra-aesthetic, strong uniqueness and characteristics, hence it can contribute to enriching the local and national culture.